Elements of Multimodal Didactics: Lecture Casting - Alexander Schmoelz (Forum Neue Medien in der Lehre Austria, 2014)
The introduction of information and communication technology (ICT) and new media to teaching and learning has been at the forefront of debates on didactics. Yet, another important idea-multimodal didactics-is clearly on the rise. Research on literacy and didactics primarily draw on linguistic and textual aspects, but increasingly important are modes of meaning other than linguistic, including visual, audio gestural, spatial and multimodal meanings. This paper explores in how far the introduction of lecture casting can be seen as a step toward multimodal didactics? Therefore the Lecture Casting Project, present data on the strengths and developments of the project, the integration of lecture casting in didactical designs and the comparison of research finding with in-house developments will be laid out to suggest possible didactical and pedagogical improvements in regards to multimodality. 24.04.2014 | Alexander Schmoelz (Vienna)